POINT-WISE CONVERGENCE OF INVERSE INTEGRAL WAVELET TRANSFORM UNDER DINI CONDITION - O. V. Doubrovina (Наука и техника)
The paper develops a formula for an inversion of the integral wavelet transform in the space of square-summed-up functions and reveals a point-wise convergence of the inverse wavelet transform under Dini condition.